2017
DOI: 10.2139/ssrn.3041335
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Well-Being and Partnership Dynamics; Are Same-Sex Relationships Different

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…It is known marriage benefits men and women in heterosexual relationships-they are healthier and happier than single individuals (Grover & Helliwell, 2019). Studies about the benefits of same-sex marriage show marital advantages for same-sex couples as well (Chen & Van Ours, 2018). Carpenter et al (2018) found that being married increased healthcare access and care among sexual minority men in the United States.…”
Section: Same-sex Familiesmentioning
confidence: 99%
“…It is known marriage benefits men and women in heterosexual relationships-they are healthier and happier than single individuals (Grover & Helliwell, 2019). Studies about the benefits of same-sex marriage show marital advantages for same-sex couples as well (Chen & Van Ours, 2018). Carpenter et al (2018) found that being married increased healthcare access and care among sexual minority men in the United States.…”
Section: Same-sex Familiesmentioning
confidence: 99%